Does IL-1F5 have anti-inflammatory actions in the brain? - Costelloe, Céire E. (Trinity College (Dublin, Ireland). Department of Physiology, 2007)
Similarity in structure and sequence homology has led to the identification of additional members of the IL-1 ligand and receptor superfamilies. Because of the importance of IL-1 in immune and inflammatory reactions, elucidation of the respective roles of these recently described members is a priority. Thus far identification of a biological role for IL-1F5 has remained elusive. In this thesis investigation into a possible role for IL-1F5 in neuronal tissue was carried out and the findings of this study suggest that IL-1F5 abrogates IL-1β-induced inhibition of Long term potentiation (LTP), and associated increase in activation of c-Jun N terminal kinase (JNK). The data also show that IL-1F5 antagonizes the inhibitory effect of lipopolysaccharide (LPS) on LTP in rat dentate gyrus. The data indicate that this is associated with its ability to inhibit the LPS-induced activation of microglial cells and, as a consequence inhibit the increase in IL-1β and JNK.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin